Hypoglossal Nerve Stimulation and Heart Rate Variability: Analysis of STAR Trial Responders. (January 2019) - Dedhia, Raj C.; Shah, Amit J.; Bliwise, Donald L.; Quyyumi, Arshed A.; Strollo, Patrick J.; Li, Qiao; Da Poian, Giulia; Clifford, Gari D.
Objective: Hypoglossal nerve stimulation represents a novel therapy for the treatment of moderate-severe obstructive sleep apnea; nonetheless, its cardiovascular effects are not known. We examine the effects of hypoglossal nerve stimulation on heart rate variability, a measure of autonomic function. Study Design: Substudy of the STAR trial (Stimulation Therapy for Apnea Reduction): a multicenter prospective single-group cohort. Setting: Academic and private practice centers in the United States and Europe. Subjects and Methods: A subset of responder participants (n = 46) from the STAR trial was randomized to therapy withdrawal or therapy maintenance 12 months after surgery. Heart rate variability analysis included standard deviation of the R-R interval (SDNN), low-frequency power of the R-R interval, and high-frequency power of the R-R interval. Analysis was performed by sleep with 5-minute sliding window epochs during baseline, 12 months, and the maintenance/withdrawal period. Results: A significant improvement from baseline to 12 months in heart rate variability was seen for SDNN and low frequency across all sleep stages. SDNN analysis demonstrated no change in the wake period (mean ± SD: 0.042 ± 0.01 vs 0.077 ± 0.07, P = .19). Reduction in SDNN was correlated to improvement in apnea-hypopnea index ( r = 0.39, P = .03). In the therapy withdrawal group, no significant changes in SDNN were seen for N1/N2, N3, or rapid eye movement sleep. Conclusion: Hypoglossal nerve stimulation therapy appears to reduce heart rate variability during sleep. This reduction was not affected by a 1-week withdrawal period. Larger prospective studies are required to better understand the effect of hypoglossal nerve stimulation on autonomic dysfunction in obstructive sleep apnea.